Analisis Pengaruh Bentuk Mata Tool Punch Terhadap Gaya Dan Kualitas Pemotongan Pada Proses Blanking - Lubis, Fahri Asrizal; Yohanes, Yohanes (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
presses (punch) and mold (dies). In the process of blanking the shape of the workpiece (product) that is produced is round in the form of slabs, this form is the simplest easily measured and observed. Burr (sharpangle on the cutting edge of the sheet) is one of the characteristics of the results of cutting on the part of the workpiece (product) formed in the blanking process, these characteristics are influenced by the type of material,clearance dies, sharpness and shape of the eye tool punch. There are three criteria for failing or safe burr formation, which are categorized as good judgments if the burr height is very small, categorized as mediumrating if the height of burr approaches the limiting curve but still in the area of the safe curve, it is categorized as bad if the height of the burr is very large. In this study the blanking process uses mild steel plates with a platethickness of 1.5 mm. The punch tool used is four, namely the punch tool A, B, C, and D. The tool punch materialuses HSS with a diameter of 16 mm while for dies using AISI 4340. The clearance dies used is 0,09 mm. From the results of the research that has been done, it can be concluded that the blanking process using the punch tool requires a working pressure of 115 bar with the smallest burr height of 0,12 mm and the largest of 0,47 mm. The blanking process using the punch B tool requires a working pressure of 50 bar with the smallest burrheight of 0,10 mm, and the largest of 0,24 mm. The blanking process using the punch C tool requires a working pressure of 119 bar with the smallest burr height of 0,55 mm and the largest of 0,75 mm. The blanking processusing the punch D tool requires a working pressure of 60 bar with the smallest burr height of 0,15 mm and the largest of 0,36 mm.Keywords: Blanking Process, Tool Punch, Dies, Burr